Mechanical Characterization of Micrometric Chitosan-Coated Vesicle by Atomic Force Microscopy - Rinaudo, M.; Quemeneur, Francois; Dubreuil, F.; Fery, Andreas; Pepin-Donat, B. (International Journal of Polymer Analysis and Characterization, 2013)
This article reports the main results obtained for the stabilization of DOPC liposomes by coating with chitosan. We investigated the compression between two planes of isolated GUV, combining force spectroscopy measurements with scanning probe microscopy (SPM) and epifluorescence microscopy observations. We obtained reproducible and reversible force-deformation curves for individual vesicles in the range of small deformation (relative deformation up to 0.3). Force-deformation curves were analyzed using a simple elastic model, which well describes the observed radius-dependency of the force response and allows determining the stretching modulus for bare vesicle and effective bending and stretching moduli for chitosan-coated membranes. Results first show that chitosan coating increases the effective stretching modulus of the lipid membranes, second, confirm that chitosan is adsorbed flat on the membrane, and finally lead us to assume that the chitosan coating structure can be regarded as a physical network of connected chitosan patches. © 2013 Copyright Taylor and Francis Group, LLC.
CRIS-Team Scopus Importer:2023-03-20
Keywords: AFM; DOPC lipid vesicle; Mechanical parameters; Mechanism of chitosan adsorption